Increased Chondroitin Sulfate Proteoglycan Expression in Denervated Brainstem Targets Following Spinal Cord Injury Creates a Barrier to Axonal Regeneration Overcome by Chondroitinase ABC and Neurotrophin-3 - Massey, James M. (2007)
Increased chondroitin sulfate proteoglycan (CSPG) expression in the vicinity of a spinal cord injury (SCI) is a primary participant in axonal regeneration failure. However, the presence of similar increases of CSPG expression in denervated synaptic targets well away from the primary lesion and the subsequent impact on regenerating axons attempting to approach deafferented neurons has not been studied. Constitutively expressed CSPGs within the extracellular matrix and perineuronal nets of the adult rat dorsal column nuclei (DCN) were characterized using real-time PCR, western blot analysis and immunohistochemistry. We show for the first time that by 2 days and through 3 weeks following SCI, the levels of NG2, neurocan and brevican associated with reactive glia throughout the DCN were dramatically increased throughout the DCN despite being well beyond areas of trauma-induced blood brain barrier breakdown. Importantly, regenerating axons from adult sensory neurons microtransplanted 2 weeks following SCI between the injury site and the DCN were able to regenerate rapidly within white matter (as shown previously by Davies et al., 1999) but were unable to enter the denervated DCN. Application of chondroitinase ABC or neurotrophin 3-expressing lentivirus in the DCN partially overcame this inhibition. When the treatments were combined, entrance by regenerating axons into the DCN was significantly augmented. These results demonstrate both an additional challenge and potential treatment strategy for successful functional pathway reconstruction after SCI.